Hotel Employees' Competencies and Qualifications Required According to Hotel Divisions / Youngmi Kim ...[et al.] - Kim, Youngmi; Kim, Samuel Seongseop; Seo, Jeongmo; Hyun, Jaechun (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
The concept of competency is becoming increasingly more important in human resource management in many industries. The hotel industry also responds in like manner to the use of competencies in human resource management as this industry is people focused and labor intensive. Thus, people with the level of proficiency and types of skills are highly required for a successful business. To some degree, this study attempted to explore hotel employees' competency as well as qualcations according to hotel divisions: General Management; Marketing & Sales; Rooms Division; F&B; and Cooking. The result of factor analysis using 34 competency items produced seven competency dimensions. This study also proved that different types of competencies or qualifications were most necessary for each department. Therefore, the findings will help hoteliers in the future to understand the job requirements for each department in a hotel.